The ideological interface between Psalm 1 and Psalm 2 - Botha, Phil J. (Old Testament essays, 2005)
This article is a social-scientific investigation of the ideology displayed in Psalm 1 and the ideology displayed in Psalm 2. It endeavours to describe the ideological points of contact between the two psalms, so as to determine the possible ideological point of view of the editor who juxtaposed the two psalms to form an introduction to the book of Psalms as a whole. The article concludes that the editor of the Psalms propagated a view of Yahwism as presupposing and necessitating a theocratic society, both nationally and internationally.